Insights into effects of individual, dyadic, and collaborative planning interventions on automatic, conscious, and social process variables. (December 2022) - Kulis, Ewa; Szczuka, Zofia; Banik, Anna; Siwa, Maria; Boberska, Monika; Knoll, Nina; Radtke, Theda; Scholz, Urte; Rhodes, Ryan E.; Luszczynska, Aleksandra
Abstract: Objective: Going beyond the effects of individual planning ("I-for-me"), we investigate the associations of dyadic ("we-for-me") and collaborative ("we-for-us") planning with automatic, conscious, and social process variables that may elucidate the differences through which these three types of planning operate. We tested the effects of three planning interventions on: (1) habit strength, representing an automatic process, (2) the use of individual planning, representing a conscious process, (3) the use of collaborative planning, representing conscious and social processes, and (4) collaborative social control, representing a social process. Methods: N = 320 adults were randomly assigned to one of four conditions: (1) the active control condition, (2) the individual planning condition, (3) the dyadic planning condition, or (4) the collaborative planning condition. Self-reported data on habit strength, the use of individual planning, the use of collaborative planning, and collaborative social control were assessed at baseline and at the 9-week follow-up. Analyses used linear mixed modelling. Results: Compared to the control group, participants in the individual planning condition had stronger habits at the 9-week follow-up. Those in the dyadic planning condition reported higher levels of the use of collaborative planning and higher levels of collaborative social control at the follow-up. Finally, compared to those assigned to the control group, participants in the collaborative planning condition reported stronger habits, higher levels of the use of both individual and collaborative planning, and higher levels of collaborative social control at the follow-up. Conclusions: Individual, dyadic, and collaborative planning interventions may result in distinct patterns of changes in the variables representing automatic, conscious, and social processes. In particular, changes in automatic, conscious and social process variables, evoked by the collaborative "we-for-us" planning intervention may reflect the major regulatory effort of forming joint plans and subsequently integrating regular joint exercise into the weekly schedule. Highlights: Plans may be individual (I-for-me), dyadic (we-for-me) or collaborative (we-for-us). Distinct effects on automatic, conscious, social regulatory variables were tested. Individual planning resulted in an increase of physical activity habit. Dyadic planning triggered the use of collaborative plans and collaborative control. Collaborative planning resulted in an increase of all 3 types of processes.